Neurological Complications of Leprosy - Lau, K. H. Vincent (Seminars in Neurology, 2019)
Leprosy is a challenging international health concern. Despite tremendous efforts in reducing worldwide disease prevalence in the past decades, some countries remain endemic and are plagued by high levels of disability. The neurological complications of leprosy are varied and complex, with current research focused on evaluating tools for earlier diagnosis of neuropathy, especially in resource-limited countries. While treatment with multidrug therapy is highly effective, active research aims to simplify regimens to improve adherence, minimize adverse effects, and prevent antimicrobial resistance. Although promising progress has been made in the past decades, further efforts are needed to push the international community toward achieving worldwide elimination.
Keywords: leprosy; mycobacterium; peripheral neuropathy; autonomic neuropathy; small fiber neuropathy